การบริหารเชิงกลยุทธ์สู่การเป็นสถานศึกษารางวัลพระราชทาน ระดับประถมศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาอุดรธานี เขต 4 - อาษาศรี, วรพงษ์; ชมภูวิเศษ, พัชรินทร์ (วารสารการบริหารการศึกษา มมร.วิทยาเขตร้อยเอ็ด; Vol 4 No 3 (2567): กันยายน-ธันวาคม 2567, 2024)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษากระบวนการการบริหารเชิงกลยุทธ์สู่การเป็นสถานศึกษารางวัลพระราชทาน ระดับประถมศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาอุดรธานี เขต 4 การวิจัยในครั้งนี้ใช้ระเบียบวิธีวิจัยเชิงคุณภาพ วิธีกรณีศึกษาจากโรงเรียนที่ได้รับรางวัลสถานศึกษาพระราชทาน ระดับประถมศึกษา คือ โรงเรียนบ้านท่าโสม เก็บรวบรวมข้อมูลและวิเคราะห์ข้อมูล ด้วยการวิเคราะห์เอกสาร การสัมภาษณ์เชิงลึก การสังเกต การจดบันทึก และการวิเคราะห์เนื้อหา โดยเก็บข้อมูลจากบุคลากรหลักในสถานศึกษา จำนวน 5 คน ผู้มีส่วนได้เสีย จำนวน 2 คน ผู้ทรงคุณวุฒิ จำนวน 2 คน โดยใช้การตรวจสอบข้อมูลแบบสามเส้าเพื่อยืนยันความเชื่อมั่น ความเที่ยงตรงของข้อมูล ความถูกต้องและความเชื่อถือได้ ผลการวิจัยพบว่า กระบวนการการบริหารเชิงกลยุทธ์สู่การเป็นสถานศึกษารางวัลพระราชทาน ระดับประถมศึกษา ประกอบด้วย 1) การวิเคราะห์สภาพแวดล้อม มีการวิเคราะห์สภาพแวดล้อมภายในและภายนอก (SWOT Analysis) เพื่อวางแผนการพัฒนาคุณภาพผู้เรียน ผลสัมฤทธิ์ทางการเรียนและคุณลักษณะอันพึงประสงค์ตามบริบทสถานศึกษา โดยการมีส่วนร่วมของทุกฝ่ายที่เกี่ยวข้อง 2) การกำหนดทิศทางองค์กร มีการนำข้อมูลจากการวิเคราะห์สภาพแวดล้อมมากำหนดทิศทางการพัฒนาสถานศึกษา มีภารกิจและเป้าหมายที่มุ่งเน้นด้านความเป็นเลิศทางวิชาการของผู้เรียนและส่งเสริมผู้เรียนให้มีศักยภาพในการแข่งขันและสอดคล้องกับบริบทสถานศึกษา 3) การกำหนดกลยุทธ์ มีการนำทิศทางการพัฒนาสถานศึกษา พัฒนาเป็นแนวทางและวางแผนเพื่อตัดสินใจในการบริหารสถานศึกษา กำหนดวิสัยทัศน์ พันธกิจ เกี่ยวข้องกับคุณภาพนักเรียนโดยตรงและมุ่งเน้นการพัฒนาสู่คุณภาพมาตรฐานสากล 4) การนำแผนกลยทธ์ไปปฏิบัติ มีการประชุม วางแผน จัดทำโครงการและกิจกรรมที่ส่งผลต่อคุณภาพผู้เรียนโดยเน้นผู้เรียนเป็นสำคัญ กำหนดบทบาทหน้าที่ชัดเจนเป็นระบบ เกิดเอกลักษณ์และอัตลักษณ์ของสถานศึกษาอย่างเป็นรูปธรรม 5) การติดตามและประเมินผลกลยุทธ์ มีการนิเทศ กำกับ ติดตาม การดำเนินโครงการและกิจกรรมตามแผนกลยุทธ์ของสถานศึกษา โดยเน้นการมีส่วนร่วม ผู้รับผิดชอบจัดทำรายงานเพื่อนำข้อมูลมาประกอบการวางแผนในปีการศึกษาถัดไป ปรับเปลี่ยน พัฒนาโครงการ กิจกรรมตามความเหมาะสมกับบริบทของสถานศึกษา The objectives of this research were: Study the Strategic Management processes to toward Royal Awarded of Primary School. This research using Qualitative research methodology and case study from a school that has received the royal award for educational institutions at the primary school level, namely Banthasom School. Collect and analyze data through document analysis, in-depth interviews, observation, note-taking, and content analysis by gathering information from 5 key personnel in the educational institution, 2 stakeholders, and 2 experts. A triangulation method was used to verify the credibility, accuracy, and reliability of the information. The results of the research were as follows: The strategic management processes to toward Royal Awarded of Primary School. include: 1) Environment analysis involves analyzing both internal and external environments (SWOT Analysis) to plan the development of student quality, learning outcomes, and desirable characteristics according to the context of the educational institution, with the participation of all relevant parties. 2) Set organization direction involves using data from the environmental analysis to determine the direction for the development of the educational institution, with missions and goals focused on academic excellence for students and promoting students' potential for competitiveness, in accordance with the context of the educational institution. 3) Strategy formulation the direction of educational development is developed as a guideline and plan for decision making in educational administration, vision and mission are set, directly related to student quality and focus on development towards international standard quality. 4) Strategy implementation there are meetings, plans, projects and activities that affect the quality of students, focusing on students as the most important factor, defining clear roles and responsibilities systematically, and creating a tangible identity and identity of the educational institution. 5) Strategy evaluation and control there is supervision, monitoring and follow-up of the implementation of projects and activities according to the strategic plan of the educational institution, emphasizing participation. The responsible person prepares reports to use as information for planning the next academic year, adjusts, develops projects, activities as appropriate to the context of the educational institution.